Ornithology, Anthropology, and the History of Medicine in Casey Wood's Asian and Pacific Travels and Collections, c.1920-36 - Winterbottom, Anna (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2022)
Casey Wood's retirement allowed him time to expand his horizons, both in terms of his travel and the scope of his intellectual enquiries. His ornithological interests in Fiji in the South Pacific and Ceylon (now Sri Lanka) in South Asia led him to fund the production of two large-scale collections of paintings illustrating the birds of these two islands. Both original collections were reserved for the Blacker-Wood library, but in Ceylon, these paintings also formed the basis of The Coloured Plates of the Birds of Ceylon, published between 1927 and 1935. In Ceylon and Kashmir, Wood collected manuscripts and lithographs, mainly relating to the history of medicine. His collection of palm-leaf manuscripts (olas) from Ceylon was particularly extensive, with over 220 remaining in the Osler and Rare Books and Special Collections branches of the McGill libraries. Wood also collected physical objects, beginning with bird skins, nests, and eggs in Fiji and branching out to include objects associated with healing in Ceylon. The object from Ceylon, numbering around 200, were originally collected for the Medical Museum and are now housed in the Redpath Museum at McGill. They represent a unique resource for the material culture of medicine. Wood's travels brought him into contact with a wide range of people, from the American plant prospector David Fairchild to Rabindranath Tagore, a central figure in the Bengali renaissance. Wood's reflections on his journeys provide some interesting insights into practices of natural history and collecting in late colonial societies on the brink of the second world war.